2010
DOI: 10.1016/j.toxlet.2010.03.1115
|View full text |Cite
|
Sign up to set email alerts
|

Human placental glutathione S-transferase activity and polycyclic aromatic hydrocarbon DNA adducts as biomarkers for environmental oxidative stress in placentas from pregnant women living in radioactivity- and chemically-polluted regions

Abstract: This study was designed to analyze the effect of environmental oxidative stress on human placental monooxygenases, glutathione S-transferase (GST) activity and polycyclic aromatic hydrocarbon (PAH)–DNA adducts in human term placentas from radioactivity-contaminated and chemically-polluted areas of the Ukraine and Belarus, and to compare these biomarkers to the newborn’s general health status. Placental PAH–DNA adduct formation, GST activity, 7-ethoxycoumarin O-deethylase (ECOD) activity, and thiobarbituric rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 19 publications
1
18
0
1
Order By: Relevance
“…Lastly, gene polymerase (DNA directed), gamma 2, accessory subunit ( POLG2, CN440810, OLIGO_08124) is important during the blastocyst stage for mitochondrial DNA transcription and replication (Lloyd et al 2009). These results are consistent with multiple studies that reported under-expression of genes with transferase activity in placental and embryo samples from abnormal relative to normal pregnancies in human and mouse (Prokopenko et al 2002; El-Bassiouni et al 2005; Toledo et al 2006; Rausell et al, 2007; Obolenskaya et al 2010). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Lastly, gene polymerase (DNA directed), gamma 2, accessory subunit ( POLG2, CN440810, OLIGO_08124) is important during the blastocyst stage for mitochondrial DNA transcription and replication (Lloyd et al 2009). These results are consistent with multiple studies that reported under-expression of genes with transferase activity in placental and embryo samples from abnormal relative to normal pregnancies in human and mouse (Prokopenko et al 2002; El-Bassiouni et al 2005; Toledo et al 2006; Rausell et al, 2007; Obolenskaya et al 2010). …”
Section: Discussionsupporting
confidence: 92%
“…Two examples of this situation are the relative expression level of 1) genes that have transferase activity function between reproductive technologies and 2) genes that are part of system development processes between developmental stages. With respect to the former case, multiple studies have reported difference in the expression of genes that have transferase activity function between normal and abnormal pregnancies at particular stages of mammalian development or tissues sources (Prokopenko et al 2002; El-Bassiouni et al 2005; Toledo et al 2006; Rausell et al, 2007; Obolenskaya et al 2010). However, no study has looked at the differences across stages or tissue sources.…”
Section: Introductionmentioning
confidence: 99%
“…7-Ethoxycoumarin O-deethylation (ECOD) activity was 7-fold and 2-fold higher in human placental microsomes samples (at term) from radioactivity-contaminated areas compared to a region considered to be “clean.” It was suggested that this effect could be related to the increased formation of reactive metabolites in placenta [54]. Experiments performed using animal models (chronic contamination of rats for 9 months by depleted uranium as uranyl nitrate in drinking water, dose of 1 mg/rat/day) showed that the cholesterol-oxidizing enzyme CYP46A1 displayed a 39% increase in mRNA level, as determined by RT-PCR [36].…”
Section: Tabular Presentationmentioning
confidence: 99%
“…7 It has been revealed that enhanced GST activity in placenta is more beneficial for the health of the newborn. 8 GST exhibits several allelic variants and GSTT1 and GSTM1 are prominent among them. GSTT1/M1 polymorphism has been shown to affect the enzymatic activity and therefore may have some bearing in IFGR.…”
Section: Introductionmentioning
confidence: 99%